Inheritance and alteration of transforming DNA during an induced parasexual cycle in the imperfect fungus Cladosporium fulvum - Arnau, J.; Oliver, Richard (1993)
Protoplasts of a pAN7-1-transformed isolated of Cladosporium fulvum race 4, harbouring a tandem duplication of the vector, and an untransformed race 5 isolate were fused, without selection for the presence of vector sequences. Fusion products were allowed to haploidize spontaneously. The inheritance of pAN7-1 sequences and the expression of the hph gene was studied in 85 progeny. A very high proportion (80%) of the progeny contained vector sequences and 70% of the progeny were resistant to hygromycin. Inactivation of the hph gene occurred in eight progeny. Rearrangement of vector sequences can account for the inactivation: there is no evidence for any RIP-like mechanism. A number of novel bands were observed.